On the issue of the development of domestic tourism in the Russian Federation - N. S. Sergienko (Вестник университета)
The article considers the problematic issues of the development of the tourism industry in the Russian Federation. In the context of global challenges, the tourism sector of the Russian Federation retains significant potential to accelerate growth and strengthen its role in the development of the economy. On the example of individual tourist projects, the author summarizes and identifies possible areas of activity of public authorities. The study makes comprehensive proposals for the development of the tourist destination at the territorial level, including in the preparation of strategic documents, the adoption of regulatory measures on the business activities of the self-employed in the tourism sector, increasing the revenue base of local budgets through the development of tourism through the introduction of an additional fee.